STRATIGRAPHY OF THE CARNIAN - NORIAN CALCARI CON SELCE FORMATION IN THE LAGONEGRO BASIN, SOUTHERN APENNINES (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
The Upper Triassic Calcari con Selce Formation, cropping out in the southern Apennines (S Italy), consists of 400 m of micritic limestones, often nodular, with chert beds and nodules, organized in dm to m beds intercalated with mm (rarely centimetric) marly horizons. Three intervals characterized by higher siliciclastic content have been recognized within this formation, and stratigraphically ordered after an accurate conodont biostratigraphical investigation: 1) the green clay-radiolaritic horizon, previously named in literature with the informal expression of “livello argilloso ad Halobia superba”, Tuvalian (upper Carnian); 2) an interval of some tens of meters of limestones and brown shales with abundant chert beds, here informally termed the "brown member", Tuvalian/Lacian (upper Carnian/lower Norian; 3) the ca. 3 m thick red shale horizon, Sevatian (upper Norian) in age. All these intervals are characterized by micritic limestones or marly limestones with bivalves, radiolarians and conodonts alternating with shales (green, brown or red) having thicknesses of 50 cm or more. These intervals are also associated to an increase of calciturbidites, consisting of echinoderm fragments, isolated thin-shelled bivalves and reworked, partially lithified intraclasts of the Calcari con Selce Fm. The Carnian green clay-radiolaritic horizon and the Sevatian red siliciclastic interval are useful lithostratigraphic markers recognizable throughout the Lagonegro Basin and have been used as guide horizons to evaluate the lateral continuity of contiguous limestone beds. The green clay-radiolaritic horizon has been logged in 4 sections (Pignola 2, Mt. Armizzone, Pezza la Quagliara, San Michele). The sections are presently at approximately 50 km distance - but Tertiary thrusts occur between the sections, suggesting a larger separation at the time of the deposition of the Formation. Above the green clay-radiolaritic horizon, single carbonate beds or banks with the same stratigraphic position and common characteristics are recognizable in all sections. The thickness of these limestone beds may vary, but the shale interlayers and cherty beds are identical, thus, the carbonate beds have been correlated. The stratigraphic interval comprising the Sevatian red shale horizon has been acquired in two sections separated by 7 km, Monte Buccaglione (i.e lower portion of the Sasso di Castalda section) and Monte Cugnone, with a Terrestrial Laser Scanner (TLS). TLSs produce high resolution and high accuracy 3D representations of outcrops, stored as point-clouds. A regular sequence of limestone beds and shale interlayers, distinguished because of their different reflectance, has been recorded below the red shale horizon, and the thickness of single carbonate banks resulted identical within the instrumental resolution. Calcareous beds or banks thus can be correlated at the basinal scale. This implies that the Lagonegro Basin is characterized by laterally continuous carbonate sedimentation, most probably controlled by allocyclic factors, providing potential for cyclostratigraphic investigations. Original papers
Keywords: Calcari con Selce; Stratigraphy; Terrestrial Laser Scanner; Bedding pattern; Upper Triassic; Lagonegro Basin